PENGARUH PEMBERIAN KOMPOS KULIT DURIAN DAN KOMPOS KULIT KAKAO PADA ULTISOL TERHADAP BEBERAPA ASPEK KIMIA KESUBURAN TANAH - Volmer Damanik; Lahuddin Musa; Posma Marbun (Jurnal Agroekoteknologi, 2013)
Ultisol is a quite large of soil and have many constraints to be used as agricultural soil. Some of theconstraints are: Low level of the organic content, soil acidity, high level of Al saturation and lowCEC so that this land productivity is quite low. To increase the productivity can be done by increasethe availability of nutrient by adding organic compost i.e. Durian Shell compost and Cacao Shellcompost. The experiment was conducted in Completely Randomized Design methode with 3replications consistedof nine treatment. I.e by adding Durian’s Shell compost and Cacao’s Shellcompost consisting of ;1,5 g (Z1), 3,0 g (Z2), 4,5 g (Z3), 6,0 g (Z4)Durian’s Shell compost in every300 g Ultisol, and 1,5 g (C1), 3,0 g (C2), 4,5 g (C3), 6,0 (C4) Cacao’s Shell in every 300 g Ultisol,and Blanko treatment (Z0). The result shows that the addition of Durian’s Shell Compost andCacao’s Shell Compost give very real effect on Al-dd, and generally tend to increase the pH, CEC,Organic C, Total N of the soil and decrease the level of exchangeable Al.Keywords: ultisol, compost, aspects of soil fertility